Moisture Absorption Effects on Mode II Delamination of Carbon/Epoxy Composites - Wong, King Jye; Johar, Mahzan; Koloor, Seyed Saeid Rahimian; Petrů, Michal; Tamin, Mohd Nasir (Polymers, 2020)
It is necessary to consider the influence of moisture damage on the interlaminar fracture toughness for composite structures that are used for outdoor applications. However, the studies on the progressive variation of the fracture toughness as a function of moisture content M (%) is rather limited. In this regard, this study focuses on the characterization of mode II delamination of carbon/epoxy composites conditioned at 70 °C/85% relative humidity (RH). End-notched flexure test is conducted for specimens aged at various moisture absorption levels. Experimental results reveal that mode II fracture toughness degrades with the moisture content, with a maximum of 23% decrement. A residual property model is used to predict the variation of the fracture toughness with the moisture content. Through numerical simulations, it is found that the approaches used to estimate the lamina and cohesive properties are suitable to obtain reliable simulation results. In addition, the damage initiation is noticed during the early loading stage; however, the complete damage is only observed when the numerical peak load is achieved. Results from the present research could serve as guidelines to predict the residual properties and simulate the mode II delamination behavior under moisture attack.
Keywords: carbon/epoxy composite; fracture toughness; moisture absorption; delamination; cohesive zone modeling; Fickian